Question
upstudy study bank question image url

Quadratic Formula (Rational Solutions) Score: 4/10 Penalty: none Question \( 6 c^{2}-c-15=0 \) Use the quadratic formula to solve. Express your answer in simplest form. \[ \text { Show Examples } \]

Ask by Cook Ray. in the United States
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are \( c = \frac{5}{3} \) and \( c = -\frac{3}{2} \).

Solution

To solve the quadratic equation \( 6c^{2} - c - 15 = 0 \) using the quadratic formula, we follow these steps: ### Step 1: Identify coefficients The standard form of a quadratic equation is \( ax^2 + bx + c = 0 \). In our case: - \( a = 6 \) - \( b = -1 \) - \( c = -15 \) ### Step 2: Write the quadratic formula The quadratic formula is given by: \[ c = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] ### Step 3: Calculate the discriminant First, we need to calculate the discriminant \( D = b^2 - 4ac \): \[ D = (-1)^2 - 4 \cdot 6 \cdot (-15) \] ### Step 4: Substitute values into the discriminant Now, let's calculate \( D \): \[ D = 1 - 4 \cdot 6 \cdot (-15) \] \[ D = 1 + 360 \] \[ D = 361 \] ### Step 5: Apply the quadratic formula Now we can substitute \( a \), \( b \), and \( D \) into the quadratic formula: \[ c = \frac{-(-1) \pm \sqrt{361}}{2 \cdot 6} \] \[ c = \frac{1 \pm 19}{12} \] ### Step 6: Calculate the two possible solutions Now we will calculate the two possible values for \( c \): 1. \( c_1 = \frac{1 + 19}{12} = \frac{20}{12} = \frac{5}{3} \) 2. \( c_2 = \frac{1 - 19}{12} = \frac{-18}{12} = -\frac{3}{2} \) ### Final Answer The solutions to the equation \( 6c^{2} - c - 15 = 0 \) are: \[ c = \frac{5}{3} \quad \text{and} \quad c = -\frac{3}{2} \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To use the quadratic formula, we start with the standard form of a quadratic equation \( ax^2 + bx + c = 0 \). For the equation \( 6c^2 - c - 15 = 0 \), we identify \( a = 6 \), \( b = -1 \), and \( c = -15 \). The quadratic formula is given by: \[ c = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] Plugging in the values: 1. Calculate the discriminant: \[ b^2 - 4ac = (-1)^2 - 4(6)(-15) = 1 + 360 = 361 \] 2. Now substitute back into the formula: \[ c = \frac{-(-1) \pm \sqrt{361}}{2(6)} = \frac{1 \pm 19}{12} \] 3. This creates two potential solutions: \[ c = \frac{20}{12} = \frac{5}{3} \quad \text{and} \quad c = \frac{-18}{12} = -\frac{3}{2} \] Thus, the simplest forms of the solutions are \( c = \frac{5}{3} \) and \( c = -\frac{3}{2} \). Imagine solving a real-world problem, like predicting the length of a parabolic bridge or a roller coaster. Engineers often utilize the quadratic formula to calculate key parameters, ensuring safety and optimal design. By accurately solving for points of intersection or maximum heights, they ensure structures are both functional and aesthetic—who knew math could look so good? When using the quadratic formula, a common pitfall is forgetting to carefully calculate the discriminant, leading to potential errors in finding the roots. Always double-check each step, especially signs, to avoid results that don’t align with your expectations. Another mistake can occur when simplifying the final form; ensure you’re expressing your solution in the simplest terms possible!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy